“M3GAN YANG MEMBADAI”: MENYINGKAP MORAL STATUS POSHUMANISME DALAM FILM M3GAN (2022) - Nugroho, Aji Royan (Sunan Kalijaga State Islamic University Yogyakarta, 2024)
Superintelligence plays an important role in the development of discourse about posthumanism. In this context, the researcher discussed posthumanism studies in the movie M3GAN (2022). The study focused on the moral status of artificial intelligence embodied robotic prototypes created by humans, namely M3GAN. In other words, how can the protocol system be implemented on M3GAN? Does M3GAN possess moral status regarding suffering, pain, autonomy, interactivity, and adaptivity? How did the humans reveal and interact with this technology in the posthumanism era as depicted in the movie? This article used the posthumanism theory from Robert Pepperell to analyze and answer the research questions. The study used descriptive qualitative data from the dialogue scenes and visual screenshots to represent the analysis results. The results of this research show that artificial intelligence in the form of the M3GAN prototype has moral status, such as autonomy, interactivity, and suffering. It becomes a dystopian reality for the robotic creator. Furthermore, the ethics of artificial intelligence or superintelligence must be unveiled wisely in the implementation.